Disappearance of sexual dimorphism in triptolide metabolism in monosodium glutamate treated neonatal rats - Liu, Li; Jiang, Zhenzhou; Huang, Xiaofeng; Liu, Jing; Zhang, Juan; Xiao, Jingwei; Bao, Qingli; Wen, Jing; Zhang, Shuang; Zhu, Dan; Zhang, Pinghu; Zhang, Luyong (Arzneimittelforschung, 2011)
Triptolide (CAS 38748-32-2), a major active component of Tripterygium wilfordii Hook F (TWHF), was reported to be sex-dependently metabolized mainly due to sex-related expression of CYP3A2. Sexual dimorphism in the expression of CYP isoforms is affected by sex difference in daily rhythm of growth hormone (GH) secretion. Neonatal administration of monosodium glutamate (MSG) can produce latent developmental defects in GH secretion and associated sex-dependent hepatic enzymes. In the present study, the triptolide metabolism, CYP3A2 expression and CYP3A-dependent activity were evaluated in Sprague-Dawley rats treated neonatally with MSG (4 mg/g) or saline (control) on postnatal days 1, 3, 5, 7 and 9. Treatment with MSG during the neonatal period in both sexes caused a number of disorders characterized by stunted body growth, notable obesity and suppression of GH secretion to barely detectable levels. In addition, neonatal treatment with MSG nearly eliminated the male-specific CYP3A2 expression and significantly reduced the microsomal erythromycin N-demethylation activity in males, while having no effects on CYP3A2 protein in females. Consistent with the P450 findings, the sexual dimorphism of triptolide metabolism completely disappeared in MSG-treated rats. This suggested that neonatal MSG treatment could eliminate the sex-dependent difference in metabolism of triptolide by suppressing CYP3A2 expression and activity in males to the same extent as females.
Keywords: CAS 38748-32-2; CYP3A2; Growth hormone; Monosodium glutamate; Sexual dimorphism; Triptolide, metabolism